Ethno-pedagogical Study of Siat Sarang: A Local Wisdom Approach to Conflict Prevention - I Wayan Putra Yasa; I Wayan Suastra; Ida Bagus Putu Arnyana; Desak Made Oka Purnawati; Ketut Sedana Arta (Soshum: Jurnal Sosial dan Humaniora)
The aims of this research are to 1) reconstruct the background of the Siat Sarang tradition in the Selat Traditional Village, Karangasem, Bali, 2) explore ethno-pedagogical values ​​as character values ​​of the Siat Sarang tradition that can prevent conflict, and 3) Reconstruct a model of ethno-pedagogical practice in Siat Sarang tradition as a safety valve based on local wisdom for conflict prevention. Then, this phenomenon is studied using qualitative methods with a critical ethnographic model—data collection using in-depth interviews, observation, and literature study. Then, evaluate its validity by triangulating methods and sources. The data was then analyzed using critical ethnography, resulting in a comprehensive survey of strategies, values​​, and implementation models. The research results show that the Siat Sarang tradition has local wisdom values​​, which can be used as a safety valve to prevent societal conflict. The values ​​contained in it are religious, social, sportsmanship, and ethnic-based educational values ​​(ethno-pedagogy). These values ​​have been inculturated in families, communities, and schools. The results of this research mean that tradition has a role in preventing conflict. The form is local wisdom, which has ethno-pedagogical value in the form of character education.